Early Patient Outcomes After Primary Total Knee Arthroplasty with Quadriceps-Sparing Subvastus and Medial Parapatellar Techniques: A Randomized, Double-Blind Clinical Trial - Tomek, Ivan M. (The Journal of Bone and Joint Surgery, Inc., 2014)
BACKGROUND: Techniques that reduce injury to the knee extensor mechanism may cause less pain and allow faster recovery of knee function after primary total knee arthroplasty. A quadriceps-sparing (QS) subvastus technique of total knee arthroplasty was compared with medial parapatellar arthrotomy (MPPA) to determine which surgical technique led to better patient-reported function and less postoperative pain and opioid utilization. METHODS: In this prospective, double-blind study, 129 patients undergoing total knee arthroplasty were randomized to the QS or the MPPA group after skin incision. All surgical procedures utilized minimally invasive surgery principles and standardized anesthesia, implants, analgesia, and rehabilitation. The Knee Society Score (KSS) was obtained at baseline and one and three months after surgery. Weekly telephone interviews were used to collect patient-reported outcomes including ambulatory device use, the UCLA (University of California Los Angeles) activity score, performance of daily living activities, and opioid utilization. RESULTS: No differences between groups were seen in opioid utilization, either during the acute hospitalization or in the eight weeks after surgery. The QS group reported significantly less pain at rest on postoperative day one and with activity on day three (p = 0.04 for each). Compared with baseline, both groups showed significant improvements in the KSS at one month (MPPA, p = 0.0278; QS, p = 0.0021) and three months (p < 0.0001 for each) as well as week-to-week gains in walking independence through five weeks after surgery. Independence from ambulatory devices outside the home lagged behind independence indoors by about two weeks in both groups. CONCLUSIONS: When primary total knee arthroplasty was performed with contemporary minimally invasive surgery principles and standardized implants, anesthesia, and postoperative pathways, the QS technique yielded no significant early functional advantages or differences in opioid utilization compared with the MPPA technique. However, the mean pain scores reported by patients in the QS group were slightly lower at rest on postoperative day one and during activity on day three. LEVEL OF EVIDENCE: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.